Good Practices for Loose Part Utilization in Early Childhood Learning for ECCE Teachers at Gugus 3 Kecamatan Pondok Aren Tangerang Selatan – Banten City - Ajat, Ajat; Nuraini, Nuraini; Sa'adah, Ni'matus; Bakir, Widya Fitriani; Wahab, Nurhayati; Anggraini, Chatarina (Jurnal Pengabdian Masyarakat Formosa, 2023)
Good practice regarding the use of loose parts in early childhood learning is an innovation. Which aims to increase knowledge, skills and strategies for PAUD Teachers in Cluster 3, Pondok Aren District, South Tangerang City, Banten in utilizing loose part media for creative and effective learning. Loose Parts are objects that can be manipulated and used freely by young children in playing and learning, such as stones, rubber bands, wood and other natural materials. Implementation of this community service begins with analyzing program needs through surveys and literacy studies to identify areas that need to be improved in the use of loose parts in early childhood learning. The impact of this good practice can be adopted by PAUD teachers thereby increasing teachers' understanding and creativity in using loose parts in early childhood learning.